STRATEGIC MANAGEMENT OF UNIVERSITIES’ COMPETITIVE ADVANTAGES IN THE CONTEXT OF HIGHER EDUCATION REFORMS IN UZBEKISTAN (Universal International Scientific Journal, 2026)
his paper examines how higher education reforms reshape the competitiveenvironment of universities in Uzbekistan and why strategic management becomes decisive forsustaining and strengthening competitive advantages. The study conceptualizes universities’competitive advantages as a combination of strategic resources and capabilities (human capital, researchand innovation capacity, educational quality, partnerships, governance effectiveness, and digitaltransformation readiness) that create stakeholder value and improve institutional positioning. Using aconceptual-analytical approach based on the synthesis of international and national research, the paperdevelops a strategic framework that links reform drivers to strategic choices and measurable outcomes.The results highlight key managerial priorities: aligning institutional strategy with reform requirements,strengthening quality assurance systems, investing in academic staff development, expanding externalpartnerships, and introducing performance-based governance tools. The proposed framework can beapplied by university management to diagnose strategic gaps, select development priorities, and designorganizational and economic mechanisms that enhance competitiveness during reform
Keywords: strategic management; competitive advantage; university competitiveness